2018
DOI: 10.1371/journal.pone.0209915
|View full text |Cite
|
Sign up to set email alerts
|

Parallel but independent reduction of emotional awareness and corpus callosum connectivity in older age

Abstract: Differential functional specialization of the left and right hemispheres for linguistic and emotional functions, respectively, suggest that interhemispheric communication via the corpus callosum is critical for emotional awareness. Accordingly, it has been hypothesized that the age-related decline in callosal connectivity mediates the frequently demonstrated reduction in emotional awareness in older age. The present study tests this hypothesis in a sample of 307 healthy individuals between 20–89 years using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 75 publications
(113 reference statements)
1
27
0
Order By: Relevance
“…Expectedly, similar dissociation between the two species are also found regarding the corpus callosum. While studies on humans report a prominent decline of midsagittal callosal area (Doraiswamy et al, 1991;Hasan et al, 2008;Prendergast et al, 2015;Raz et al, 2010;Skumlien et al, 2018) or thickness (Danielsen et al, 2020), preservation of callosal area has been reported in aging chimpanzees (Hopkins et al, 2016;Hopkins & Phillips, 2010). The present study, while confirming the general differences in aging trajectories of the corpus callosum of the two species, offers a series of important clarifications and novel data to the literature.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Expectedly, similar dissociation between the two species are also found regarding the corpus callosum. While studies on humans report a prominent decline of midsagittal callosal area (Doraiswamy et al, 1991;Hasan et al, 2008;Prendergast et al, 2015;Raz et al, 2010;Skumlien et al, 2018) or thickness (Danielsen et al, 2020), preservation of callosal area has been reported in aging chimpanzees (Hopkins et al, 2016;Hopkins & Phillips, 2010). The present study, while confirming the general differences in aging trajectories of the corpus callosum of the two species, offers a series of important clarifications and novel data to the literature.…”
Section: Discussionsupporting
confidence: 81%
“…Histological studies have found a reduction in number and density of small myelinated axons (Hou & Pakkenberg, 2012) and degeneration of axonal myelin sheaths in old age (Bowley, Cabral, Rosene, & Peters, 2010;Peters & Sethares, 2002). These histological alterations are reflected in the findings of in-vivo diffusion MRI studies, which report a decrease in anisotropy and an increase in radial diffusion (i.e., orthogonal to the main fibre direction) in the aging corpus callosum (Hasan et al, 2009;Ota et al, 2006;Pietrasik, Cribben, Olsen, Huang, & Malykhin, 2020;Skumlien, Sederevicius, Fjell, Walhovd, & Westerhausen, 2018). Also, studies using high-gradient strength-based mapping of callosal fibre architecture suggest an agingassociated reduction in axon density (Fan et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…(a) The modulation of global brain connectivity and patterns of synchronization (identified as an aspect of brain self-regulation) through the rhythmic segregation and integration of neural populations acting in concert to code for complex stimuli [143][144][145][146][147][148][149]; (b) The engagement of cross-hemispheric communication via the corpus callosum, which facilitates integrative higher-order neural network processes and is implicated in the ability to verbally identify, interpret and communicate emotions [150][151][152][153][154]. (c) The simultaneous engagement of low threshold (sensitive to light touch) skin receptors from the affective-affiliative system in the mammalian nervous system, primarily composed of C-tactile fibers and/or receptors [155][156][157][158][159], polymodal C-receptors, unmyelinated free nerve endings [160] and the low threshold discriminative-spatial system, associated with Merkel's cell-neurite complex receptors and Ruffini corpuscle proprioceptors [47,137,[161][162][163][164][165].…”
Section: Final Considerationsmentioning
confidence: 99%
“…The corpus callosum as the major white-matter commissure, is a critical channel for the integration of information (e.g., Steinmann et al, 2018;Westerhausen, Gruner, Specht, & Hugdahl, 2009) and coordination of processing in the two cerebral hemisphere (e.g., Davis & Cabeza, 2015;Thiel et al, 2006). Thus, it appears little surprising that human neuroimaging studies report an association of individual differences in corpus callosum morphology with differences in higher cognitive abilities (e.g., Danielsen et al, 2020;Dunst, Benedek, Koschutnig, Jauk, & Neubauer, 2014;Hulshoff-Pol et al, 2006;Luders et al, 2007;Westerhausen et al, 2018). In the aging brain, however, these functions of the corpus callosum are affected by a progressive degeneration of callosal axons, evidenced by a reduction in number and density of small myelinated axons (Fan et al, 2019;Hou & Pakkenberg, 2012;Køster, Jesper, & Bente, 2018;Lynn et al, 2020).…”
mentioning
confidence: 99%